The Impact Non-Verbal Communication the Learning Process - Putri baroona; Purwati Purwati; Rahmiati Rahmiati; Surya Asra; Fadlia Fadlia (Journal of Education, Linguistics, Literature and Language Teaching, 2019)
This study focus on communication especially non-verbal communication that occur in classroom when teaching learning process done . The aim of this study was to find out kinds of non-verbal communication that use by two important element in learning, namely teacher and student and also to find out the impact of using the non-verbal communication to the learning process and the purpose of the study.